Nutritional, Biophysical and Physiological Characteristics of Wild Rocket Genotypes As Affected by Soilless Cultivation System, Salinity Level of Nutrient Solution and Growing Period - Bonasia, Anna; Lazzizera, Corrado; Elia, Antonio; Conversa, Giulia (Frontiers in Plant Science, 2017)
With the aim of defining the best management of nutrient solution (NS) in a soilless system for obtaining high quality baby-leaf rocket, the present study focuses on two wild rocket genotypes (“Nature” and “Naturelle”), grown in a greenhouse under two Southern Italy growing conditions—autumn-winter (AW) and winter-spring (WS)—using two soilless cultivation systems (SCS)—at two electrical conductivity values (EC) of NS. The SCSs used were the Floating System (FS) and Ebb and Flow System (EFS) and the EC values were 2.5 and 3.5 dS m−1 (EC2.5; EC3.5) for the AW cycle and 3.5 and 4.5 dS m−1 (EC3.5; EC4.5) for the WS cycle. The yield, bio-physical, physiological and nutritional characteristics were evaluated. Higher fresh (FY) (2.25 vs. 1.50 kg m−2) and dry (DY) (230.6 vs. 106.1 g m−2) weight yield, leaf firmness (dry matter, 104.3 vs. 83.2 g kg−1 FW; specific leaf area, 34.8 vs. 24.2 g cm−2) and antioxidant compounds (vitamin C, 239.0 vs. 152.7 mg kg−1 FW; total phenols, 997 vs. 450 mg GAE mg kg−1 FW; total glucosinulates-GLSs, 1,078.8 vs. 405.7 mg kg−1 DW; total antioxidant capacity-TAC, 11,534 vs. 8,637 μmol eq trolox kg−1 FW) and lower nitrates (1,470 vs. 3,460 mg kg−1 FW) were obtained under WS conditions. The seasonal differences were evident on the GLS profile: some aliphatic GLSs (gluconapoleiferin, glucobrassicanapin) and indolic 4-OH-glucobrassicin were only expressed in WS conditions, while indolic glucobrassicin was only detected in the AW period. Compared with EFS, FS improved leaf firmness, visual quality, antioxidant content (TAC, +11.6%) and reduced nitrate leaf accumulation (−37%). “Naturelle” performed better than “Nature” in terms of yield, visual quality and nutritional profile, with differences more evident under less favorable climatic conditions and when the cultivars were grown in FS. Compared to EC2.5, the EC3.5 treatment did not affect DY while enhancing firmness, visual quality, and antioxidant compounds (TAC, +8%), and reducing the nitrate content (−47%). The EC4.5 treatment reduced FY and DY and the antioxidant content. Despite seasonal climatic condition variability, FS and the moderate salinity level of NS (3.5 dS m−1) can be suggested as optimum.